RESPON TUTUR SISWA AUTIS TERHADAP TUTUR DIREKTIF GURU DALAM INTERAKSI PEMBELAJARAN DI KELAS - Siti Robiah (Universitas Muhammadiyah Ponorogo, 2017)
The purpose of this study is to describe the form, function, and response strategies said autistic students against the said directive of teachers in the learning interactions in the classroom. This study used a qualitative approach to this type of case studies. The results showed a form of response said students have two categories, namely a) manufacture a form of response aperitif response, covering the said directive, commissive, and expressive; and b) according to the type of subdivision of said response who observed, i.e. sensory response auditive, visual, and flavorings. The function of the response said the students were found in two categories, namely a) function of the response function includes the manufacture of complaining, approve, ask, ask for, stating something, showing, say thank you, apologize, asserting, reporting, States, and offering; and b) processing the occurrence response is caused by an action of the teachers giving rise to reactions from students. Furthermore, the response strategies said students found in two categories, namely a) formation of the response is determined by two factors, namely, internal and external; and b) submission of response said delivered directly.